An Evolved Control Design of Complex Systems with Multitime Delays and Multi-Interconnections - Cheng, john (International Journal of Integrated Engineering, 2019)
To guarantee the asymptotic stability of multi-time delays complex system with multi-interconnections, an evolved control design is proposed in this paper. Based on this criterion and the decentralized control scheme, a set of fuzzy controllers is then synthesized via the technique of parallel distributed compensation (PDC) to stabilize a complex system with multi-interconnections. This representation of PDC is constructed by sector nonlinearity which converts the nonlinear model to multiple rule base of the linear model and a new sufficient condition to guarantee the asymptotic stability via Lyapunov function is implemented in terms of linear matrix inequalities (LMI). Finally, a numerical example with simulations is given to demonstrate the results.